Islamic Leadership Education Program at Madrasah Tsanawiyah Husnul Khotimah 2 Kuningan - Izzuddin Hamas; Endin Mujahidin; Abas Mansur Tamam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research discusses the Islamic leadership education program run at Madrasah Tsanawiyah Husnul Khotimah 2 Kuningan. This research is motivated by the importance of leadership education to shape the character of ideal students. The purpose of this research is to see the empirical picture that occurs in the field in terms of leadership education in Madrasah Tsanawiyah so that it can be analyzed and formulated as an ideal picture for Islamic leadership education. This research is a field research that uses descriptive qualitative methods. The author collected data by distributing 19 questionnaires to students, interviewing two resource persons, and observing what happened in the field. Then the author tests the validity of the data by triangulating many sources and triangulating various techniques. Then the author analyzes it with a program approach described in eleven points, namely: Rationale, Vision and Mission, description of needs, objectives, program components, service areas, operational plans, theme/topic development, evaluation, reporting and follow-up, and budget.